La actividad emprendedora y competitividad: factores que inciden sobre los emprendedores - Galindo Martín, Miguel Ángel; MÉNDEZ PICAZO, María Teresa (Papeles de Europa, 2011)
Competitiveness in a broad sense is based on a series of pillars in which entrepreneurships play an important role. Due to this fact together with the positive relationship between entrepreneurship and economic growth it is necessary to design appropriate measures to encourage such activity. In this article, in addition to presenting entrepreneurship characteristics, we analyze the effects that fiscal and monetary policies on entrepreneurships.
Keywords: Competitiveness; Entrepreneurship; Economic growth; Fiscal policy; Monetary policy